World Economic Outlook, September 2005 : Building Institutions. - International Monetary Fund. Research Dept. (Washington, D.C. : International Monetary Fund, 2006)
The World Economic Outlook (WEO) presents the IMF's leading economists' analyses of global economic developments during the near and medium terms. It is a respected, one-stop, trusted resource offering remarkable insight, balance, and perspective to decision makers and policymakers worldwide. Published twice yearly, the World Economic Outlook presents the outlook for growth, inflation, trade, employment, and other economic developments in a clear, practical format. Each WEO considers the issues affecting advanced, emerging market, and developing economies. Central bankers, economists, Financial institutions, business leaders, governments, think tanks, and researchers eagerly await this unique investigation of what's happening and what's ahead.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet